Barriers and facilitators influencing EBP readiness: Building organizational and nurse capacity. Issue 1 (4th December 2022) - Crawford, Cecelia L.; Rondinelli, June; Zuniga, Stephen; Valdez, Regina M.; Tze‐Polo, Lisa; Titler, Marita G.
Abstract: Background: Organizational supported evidence‐based practice (EBP) enables nurses to be change agents and impact patient outcomes. Globally, a multitude of barriers limits EBP implementation, evaluation, and dissemination, which include time constraints, staff, resource access, education, technology, and fiscal support. These barriers and other disenfranchising elements hinder nurses' ability to actualize EBP and change practice within their workplace. Aims: This study describes the EBP readiness, barriers, and facilitators reported by inpatient registered nurses (RNs) employed in a nationwide healthcare system before COVID‐19. Methods: The study employed a cross‐sectional descriptive survey design using the 2005 Nursing EBP Survey for RN EBP readiness. The setting included 14 hospitals in Southern California. The survey was deployed in November 2016 and closed after 23 weeks. Descriptive statistics analyzed demographics and EBP scores, with inferential statistics for associations between demographics and EBP scores. ANOVA examined differences between EBP scores, service lines, years of employment, and education level. A content approach synthesized open‐ended barrier and facilitator questions into seven specific themes. Results: Seven hundred and twenty‐four nurses completed the survey. Overall, the scores of inpatient RNs were highest scores for Practice Climate, suggesting the health system fosters a climate conducive to EBP. Scores were lowest for Data Collection and Implementation. Qualitative themes were: (1) Everyone Involved in EBP Implementation, (2) Fear and Resistance to Change, (3) Protected Release Time, (4) Knowing EBP Culture Outside of Current Organization, (5) Organizational Communication and Education, (6) Management and Leadership Support, and (7) Pragmatic Solutions to Facilitate EBP. Fear and Resistance to Change cut across all themes. Linking Evidence to Action: Nurses at all organizational levels from the C‐suite to the bedside can create strategies to determine essential EBP readiness components, including EBP mentors to guide knowledge uptake activities. Pragmatic solutions for EBP capacity require frontline nurse feedback, commitment, and partnership with nursing leaders.